The changing face of primary care: a cross sectional study in Malaysia - Khoo, Ee Ming; Cheong, Ai Theng; Liew, Su May; Lee, Wai Khew; Abdul Samad, Azah; Mohd Hanafiah, Ainul Nadziha; Sararaks, Sondi (National University of Malaysia Press, 2015)
There has been an epidemiological transition in morbidity and mortality patterns in developing countries. This study aimed to determine whether there was an accompanying change in disease presentation in primary care. This was a cross-sectional study conducted at 12 public primary care clinics in Malaysia. Outpatient medical records were randomly selected and reviewed to identify patients’ reasons for encounter. The overall retrieval of records was 99.1% (n=1,753; range 95.7-100.0%). The mean age was 33.1 (SD 22.2) years. For all ages, the most common reasons for patient encounter (RFE) were cough (21.1%; 95% CI 16.5, 25.8), follow-up care for chronic diseases (19.6%; 95% CI 12.7, 26.6) and fever (18.4%; 95% CI 14.2, 22.5). The top RFE in West Malaysia was follow-up care for chronic diseases while in East Malaysia, the most common RFE was cough (25.2%; 95% CI 16.8, 33.6) and fever (21.7%; 95% CI 14.3, 29.0). In conclusion, there is a change in the presentation of diseases, with chronic disease emerging as one of the top RFE in primary care. In adults, for all age groups over 40 years old, care for chronic diseases has overtaken acute disease care. However, acute respiratory problems remain the overall top RFE at public primary care clinics in Malaysia. There are major differences in morbidity patterns and reasons for encounter for different age groups and geographical areas and this could be utilized for better health care planning.